CEO compensation and aggressive tax planning in China: Does firm size make a difference? - Zhang, Yuxuan; Ibrahim, Idawati; Omar, Ropidah (Edelweiss Applied Science and Technology, 2025)
This study looks at how CEO pay affects aggressive tax planning (ATP) in A-share companies in China. It also checks if the size of the company changes this effect. Using data from 2017 to 2022, the study finds that higher CEO pay leads to more ATP, and that company size plays a role in this relationship. This research adds to previous studies by showing how CEOs influence tax strategies in a growing market. It also highlights the importance of company size in corporate governance as China's economy grows. The results suggest that companies should improve how they pay executives and manage taxes, and tax authorities should pay more attention to executives and taxes as companies get bigger. Overall, this study opens up new areas for future research on CEO pay and tax behavior.